Understanding security in the government's use of blockchain technology with value focused thinking approach. Issue 3 (13th March 2020) - Tshering, Gaki; Gao, Shang
Abstract : Purpose: The purpose of the research is to assess security concerns in government's use of Blockchain technology through the lens of value focused thinking (VFT) approach. Design/methodology/approach: Qualitative methods such as open ended questions and interviews were used to gather data and the data was analysed in a structured approach to formulate a means-ends network of objectives. The data were collected from eight interviews of selected participants. Findings: The findings are 35 objectives of which ten are fundamental objectives related to the values of identity, trust, data privacy, transparency, integrity, public service delivery, cost, availability of public information, responsibility and usability. Practical implications: The study implies that governments or private organisations building blockchain solutions for governments can benefit from insights on values to focus on in blockchain security; and the current research serves as a base to understand more on blockchain use in the governments as well as security values and application of VFT approach for future academic researchers in this area. Social implications: It is a need-driven approach in which blockchain is assessed to ensure its fit to societal needs and public values. Originality/value: It is first of its kind in studying security in blockchain use by government through the lens of VFT approach, and it provides insights of values that are of importance to further blockchain use in the government.